Microvascular aspects of deep inferior epigastric perforator ﬂap revascularization in breast reconstruction - M. Ye. Sinelnikov; O. I. Starceva; D. V. Melnikov; S. I. Ivanov (Сеченовский вестник, 2019)
Because of the high incidence of breast cancer in the population, breast reconstruction remains actual after complex cancer treatment.Aim. To characterise revascularization methods based on deep inferior epigastric perforator ﬂaps (DIEP ﬂap), test the frequency and risk factors for perfusion related complications. Materials and methods. The study included 157 patients, with 190 reconstructions performed. The tactics of choosing donor and recipient vessels were determined using an intraoperative assessment of the dominant blood supply system: sample with blood ﬂow stop.Results. In most reconstructions, the deep inferior epigastric arteries were the main source of blood supply to the ﬂap. Non - standard revascularization was required in 14% of cases and was associated with prior interventions on the anterior abdominal wall or individual characteristics of its blood supply. Venous super - drainage was performed in 30% of cases. Most often, the perforating veins of the anterior chest and the retrograde pedicle of the internal chest vein were used as recipient vessels. Complete ﬂap loss occurred in 2% of cases. We observed perfusion complications in 17% of cases, statistically signiﬁcantly more often in smokers ( p